Pertanian Indonesia dalam Perundingan Aturan Perdagangan Internasional - Azahari, Delima Hasri; Panjaitan, Iskandar (UI Scholars Hub, 2021)
It is a paradox that Indonesian agriculture would prefer a market oriented condition to enhance its economic performance but at the same time it requires at significant degree of Government intervention to maintain its economic and non-economic goals to face with economic globalization. The existence of market imperfection as an argument of government intervention on agricultuer of developing countries and it is being worsened by biased trade policies applied by developed countries. By realizing its unfaded importance, Indonesia should see the paradox and consider i then makeing position for negotiations on market liberaliazation of agriculture.